Revision of Sarcophaga dissimilis Meigen, 1826 and Sarcophaga chaetoneura Brauer & Bergenstamm, 1889 (Diptera: Sarcophagidae) - Blackith, Ruth M.; Richet, René; Pape, Thomas (Zootaxa, 2004)
The two species covered by the concept of Sarcophaga dissimilis auctt. are revised and their male terminalia are illustrated. Lectotypes are designated for Sarcophaga dissimilis Meigen, 1826, Sarcophaga offuscata Meigen, 1826, and Heteronychia chaetoneura Brauer & Bergenstamm, 1889. Pierretia nigricauda Povoln & Slame kov , 1959, syn. n., and Heteronychia (Heteronychia) rohdendorfiana Mih lyi, 1975, syn. n. are considered as junior synonyms of Sarcophaga dissimilis Meigen, 1826.